Hubungan Status Gizi Dengan Lama Rawat Inap Pasien Pneumonia Balita - Rizone, Alifya Shifwah; Meirina, Fathia; Hamdi, Tasrif; Aldy, Fithria (Jurnal Kesehatan Mahardika, 2025)
Introduction: Pneumonia is known as a primary contributor to hospital admissions among toddlers globally. Numerous factors influence the duration of hospitalization in toddlers with pneumonia, one of them is nutritional status. This study aims to ascertain the correlation between nutritional status and the duration of hospitalization in pediatric pneumonia patients. Methods: This was an analytic observational study with a cross-sectional design. The study samples were children aged 2-59 months with pneumonia who were hospitalized in the period January 2022-January 2024 selected through the consecutive method. After calculating using the Slovin formula, a minimum sample size of 67 people was required. Data were analyzed through univariate analysis and bivariate analysis through chi-square through SPSS software version 27. Results: Of the 77 patients, the majority were aged 12-59 months (61%), male (55.8%), well-nourished (62.3%), and length of stay ≤5 days (55.8%). The bivariate analysis found no relationship between nutritional status and the length of stay of pneumonia patients under five with a p-value = 0.422 (p-value > 0.05). Conclusion: There is no relationship between nutritional status and the length of stay of pneumonia patients under five.